Induction of apoptosis by fenretinide (4HPR) in human ovarian carcinoma cells and its association with retinoic acid receptor expression - Rosanna Supino; Mariacristina Crosti; Mario Clerici; Andrea Warlters; Loredana Cleris; Franco Zunino; Franca Formelli (1996)
We previously reported that fenretinide (4HPR) is effective against a human ovarian carcinoma xenografted in nude mice. The effects of 4HPR on ovarian tumors have been further studied in in vitro ovarian carcinoma cell lines A2780, IGROV-I, SW626 and OVCA432. A2780 was the most sensitive line: 50% growth inhibition was obtained after 3 days of exposure to 1 μM 4HPR, a pharmacologically achievable concentration, whereas approx. 10 μM 4HPR gave a similar inhibition in the other cell lines. All-trans retinoic acid (RA), at doses up to 10 μM, did not inhibit cell proliferation. Gel electrophoresis of DNA from either detached or attached A2780 cells treated with 4HPR revealed DNA ladders in detached cells. Apoptosis was also evidenced in detached 4HPR-treated cells by flow cytometry and microscopic observation. The difference in cell line sensitivity to the anti-proliferative effect of 4HPR was not related to drug uptake or efflux. Only A2780 cells, the most sensitive to 4HPR, expressed constitutive levels of RARβ; moreover, the levels of RARα and RARγ expression in these cells were higher than in the other cell lines. In A2780 cells, the association of an IC20 of 4HPR to cisplatin resulted in a strong potentiation of the anti-proliferative effect. These data show (i) that 4HPR, in contrast to RA, has an anti-proliferative effect in human ovarian carcinoma cells which is related to induction of apoptosis and (ii) that among the tested lines, the most responsive to the drug expressed RARβ and the highest levels of RARα and RARγ. The results also suggest that 4HPR can potentiate the effects of cisplatin in ovarian carcinoma. © 1996 Wiley-Liss, Inc.